Geographic information system for reporting damage and road grouping based on website using waterfall method and k-means method - Abdullah, Dahlan; Ikhwani, Muhammad; Ardian, Zalfie; Erliana, Cut Ita; Fauzan, Muhammad; Isma, Fadilah (Edelweiss Applied Science and Technology, 2024)
Roads are a vital land transportation infrastructure and transportation route. One of the functions of roads is as a driving factor in the development process and equitable distribution of development in a region. Road damage that occurs disrupts the activities and routines of residents. Lhokseumawe City as the center of economic and social development in its region requires an efficient system for the management and maintenance of road infrastructure. The reason is that many road damages occur in Lhokseumawe City that have not been repaired due to limited damage information so reports are needed from residents to find out the location of the road damage so that it is easier for the Lhokseumawe City government to follow up on the report. With these problems, a geographic information system for reporting road damage is created. It is hoped that the government can follow up on the report and prioritize damage with the highest group, which groups road damage using the clustering method. This web-based information system is designed using the UML (Unified Modeling Language) model with the PHP programming language and uses MySQL as its database. With this system, the government can receive reports of existing damage and group the damage into three levels to determine the priority of road repairs to be carried out.